WEE1 promotes endometriosis via the Wnt/β-catenin signaling pathway - Liya Shi; Xue Xue; Hui Tian; Hongjuan Ye; Hui Wang; Rongxiang Wang; Yu Liu; Caixia Zhang; Qiuju Chen; Lihua Sun (BMC, 2021)
Abstract Background Endometriosis, the presence of active endometrial tissue outside the lining membrane of the uterine cavity, is a common disease in women of childbearing age. The ectopic endometrium has some characteristics of tumor tissue, including invasive and migratory abilities. In addition, endometriosis is associated with inflammation and reduced cellular apoptosis. Methods Western blot analysis, qPCR, immunohistochemistry, immunofluorescence microscopy, Transwell assay, wound healing assay, and TUNEL staining. Results Interleukin-1β (IL-1β) induced WEE1 expression in endometrial stromal cells (ESCs), suggesting that WEE1 may be upregulated during the endometriosis-induced inflammatory response. Overexpression of WEE1 in cultured ESCs promoted ESC migration while inhibiting apoptosis, whereas WEE1 knockdown reduced ESC migration while promoting apoptosis. Inhibition of WEE1 attenuates fibrosis in ESCs and female C57BL/6 J mice. This pro-fibrotic effect of WEE1 was significantly decreased by treatment with the Wnt/β-catenin inhibitor XAV939, suggesting that WEE1 acts via the Wnt/β-catenin signaling pathway. Conclusion Our study demonstrates that WEE1 promotes ESC migration and fibrosis via the Wnt/β-catenin signaling pathway. Thus, WEE1 may serve as a potential therapeutic target for the treatment of endometriosis.